Cognitive flexibility and its electrophysiological correlates in Gilles de la Tourette syndrome - Lange, Florian (Dev Cogn Neurosci, 2017)
Motor symptoms in Gilles de la Tourette syndrome (GTS) have been related to changes in frontostriatal brain networks. These changes may also give rise to alterations in cognitive flexibility. However, conclusive evidence for altered cognitive flexibility in patients with GTS is still lacking. Here, we meta-analyzed data from 20 neuropsychological studies that investigated cognitive flexibility in GTS using the Wisconsin Card Sorting Test (WCST). Results revealed medium-sized GTS-related performance deficits, which were significantly modulated by age: Whilst being substantial in children and adolescents with GTS, WCST deficits seem to dissolve in adult patients with GTS. This age-related normalization of WCST performance might result from the compensatory recruitment of cognitive control in adult patients with GTS. We addressed this possibility by examining neural correlates of proactive and reactive cognitive control in an event-related potential (ERP) study. We analyzed cue- and target-locked ERPs from 23 adult patients with GTS and 26 matched controls who completed a computerized version of the WCST. Compared to controls, patients with GTS showed a marked increase in parietal cue-locked P3 activity, indicating enhanced proactive cognitive control. We conclude that the additional recruitment of proactive cognitive control might ensure flexible cognitive functioning in adult patients with GTS.